Droplet departure modeling and a heat transfer correlation for dropwise flow condensation in hydrophobic mini-channels - Chen, Xi; Derby, Melanie M. (My University, 2018)
Droplet nucleation, growth, coalescence, and departure control dropwise condensation heat transfer. Smaller droplets are associated with higher heat transfer coefficients due to their lower liquid thermal resistances. Unlike quiescent dropwise condensation with gravity-driven droplet departure, droplet departure sizes in flow condensation are governed by flow-droplet shear forces and droplet-solid adhesive forces. This research models droplet departure, droplet size distributions, and heat transfer through single droplets under different flow conditions. Heat transfer through single droplets includes the thermal resistances at the vapor-liquid interface, temperature depression across the curved surface, conduction in the liquid droplet, and conduction through the surface promoter (e.g., Teflon). Droplet size distributions were determined for two ranges using the population balance method and power law function for small and large droplets, respectively. Droplet departure sizes (e.g., 10–500 µm) were derived using force balances between drag forces (obtained using FLUENT) and droplet-solid adhesive forces (determined using a third-order polynomial for contact angle distribution along contact line). The analytical model was compared to experimental flow condensation heat transfer data in a Teflon AF™-coated rectangular mini-gap with hydraulic diameters of 0.95 and 1.8 mm. The correlation was compared against experiments with a steam mass flux range of 35–75 kg/m2 s and quality of 0.2–0.9. There was good agreement between the model and experimental data; without any curving fitting, the mean absolute errors of the heat transfer correlation were 9.6% and 8.8% respectively for the 0.95-mm and 1.8-mm mini-gaps.
Citation: Chen, X., & Derby, M. M. (2018). Droplet departure modeling and a heat transfer correlation for dropwise flow condensation in hydrophobic mini-channels. International Journal of Heat and Mass Transfer, 125, 1096–1104. https://doi.org/10.1016/j.ijheatmasstransfer.2018.04.140
Keywords: Mini-channel; Dropwise condensation; Droplet dynamics; Hydrophobicity